Pelatihan Keterampilan Wirausaha Melalui Pelatihan Penggunaan Platform Online Shop untuk UMKM di Cikarang Selatan - Dhea Aulia Trifadilah; Etty Zuliawati Zed; Dea Aprilia; Amelia Yunika Putri (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
In the rapidly evolving digital era, the ability to adapt to technology is key to the sustainability and success of (MSMEs). In South Cikarang, where many business potentials have not been fully tapped, it is important to provide relevant training so that MSME players can compete in an increasingly tight market. This service activity was carried out at Seblak Mamah Farid MSME, one of the MSMEs located in the South Cikarang area, with the aim of equipping MSME players with entrepreneurial skills through training on the use of online shop platforms. With the hope that participants can utilize digital technology to increase the visibility and sales of their products. This program used a qualitative approach through indepth interviews and direct observation. Qualitative data was collected to understand participants' experiences, challenges, and expectations of the training. The results of this activity show that the training on the use of online shop platforms significantly contributes to improving participants' ability to utilize digital technology for marketing, and has a positive impact on the growth of turnover of Seblak Mamah Farid MSMEs. Thus, this program not only helps participants in improving their entrepreneurial skills, but also helps them strengthen their position in the increasingly competitive market competition.